Oscar Wilde and the Cultures of Childhood
XVIII, 245 p. 20 illus.
Keywords: This is the first collection of critical essays that explores Oscar Wilde’s interest in children’s culture, whether in relation to his famous fairy stories, his life as a caring father to two small boys, his place as a defender of children’s rights within the prison system, his fascination with youthful beauty, and his theological contemplation of what it means to be a child in the eyes of God. The collection also examines the ways in which Wilde’s works—not just his fairy stories—have been adapted for young audiences. .